Preservasi dan Konservasi Manuskrip Tradisional di Kabupaten Jember: Studi Filologi dan Digitalisasi - Gimnastiyar, Dio Islam; Baihaqi, M. Imam; Hanafi, Ahmad (Medan Resource Center, 2025)
Manuscript conservation is vital for safeguarding cultural heritage, traditional knowledge, and societal values. This study explores traditional manuscript storage and preservation practices in Jember Regency through a philological approach encompassing inventory, conservation, and digitization. Unlike previous research, this study provides a comprehensive analysis of the challenges and solutions in manuscript conservation, highlighting the intersection of traditional and modern preservation techniques. It addresses two key research questions: (1) What is the current state of manuscript culture in Jember Regency? and (2) How are manuscripts traditionally preserved in this region? Employing a philological methodology, the study involves manuscript identification, conservation initiatives, and digital preservation strategies to ensure long-term accessibility. The findings reveal that traditional storage methods significantly impact manuscript longevity, necessitating an integrated approach that merges indigenous conservation practices with digital preservation. This research contributes to manuscript preservation efforts, particularly in Jember Regency, by underscoring the role of local communities in protecting historical documents. Furthermore, the knowledge embedded within these manuscripts provides invaluable historical and cultural insights, reinforcing their significance as a foundational source for future scholarship and heritage preservation.